REPRESENTASI MEMORI KOLEKTIF PERJUANGAN KEMERDEKAAN MELALUI SASTRA LISAN - Qurrota A’yun (Journal of Linguistics, Literature, Culture and History, 2025)
Indonesia's struggle for independence has become the foundation of a national identity unified through oral literature as a medium for transmitting non-written collective memory, facing the threat of extinction in the era of globalization. This study aims to analyze representations of the independence struggle in oral literature such as the Motang Rua folktale, the Diponegoro legend, the Macapat song, and the Prang Sabi tale. It also maps the values of patriotism, colonial symbols, and mechanisms for preserving memory to strengthen national identity. A qualitative interpretive method was used, incorporating literature study and structuralist-semiotic content analysis of 20 primary texts from the archives of the Language Agency and the National Agency for Research and Innovation (BRIN), complemented by triangulation of secondary data from the Imajeri journal and regional ethnography. The results show that oral literature represents resistance through patterns of courage, solidarity, and images of sacrifice that shape nationalism. Through digital revitalization and ethnopedagogy, it has successfully overcome modern challenges for sustainable preservation